2010
DOI: 10.1111/j.1742-4658.2010.07768.x
|View full text |Cite
|
Sign up to set email alerts
|

The consensus motif for N‐myristoylation of plant proteins in a wheat germ cell‐free translation system

Abstract: Protein N‐myristoylation plays key roles in various cellular functions in eukaryotic organisms. To clarify the relationship between the efficiency of protein N‐myristoylation and the amino acid sequence of the substrate in plants, we have applied a wheat germ cell‐free translation system with high protein productivity to examine the N‐myristoylation of various wild‐type and mutant forms of Arabidopsis thaliana proteins. Evaluation of the relationship between removal of the initiating Met and subsequent N‐myris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…We confirmed that the wheat germ lysates supported N-terminal myristoylation of Gag-YFP (Fig. 1A), as reported previously (34), and that in liposome flotation assays, Gag-YFP synthesized in wheat germ lysates bound to liposomes in a PI(4,5)P 2 -dependent manner (Fig. 1B).…”
Section: Efficient Binding Of Hiv-1 Gag-yfp To Guvs Requires Treatmensupporting
confidence: 74%
“…We confirmed that the wheat germ lysates supported N-terminal myristoylation of Gag-YFP (Fig. 1A), as reported previously (34), and that in liposome flotation assays, Gag-YFP synthesized in wheat germ lysates bound to liposomes in a PI(4,5)P 2 -dependent manner (Fig. 1B).…”
Section: Efficient Binding Of Hiv-1 Gag-yfp To Guvs Requires Treatmensupporting
confidence: 74%
“…For these reactions, a plasmid encoding Gag-YFP under the control of a T7 promoter is used. Of note, as shown earlier, wheat germ lysates support myristoylation without additional components 23,24 . Using this method, it has been possible to obtain sufficient quantities of full-length myristoylated Gag-YFP for visualization of Gag on GUV membranes 24 .…”
Section: Introductionsupporting
confidence: 79%
“…Myristoylator (Bologna et al, 2004) and The MYR Predictor (http://mendel.imp.ac.at/myristate/ SUPLpredictor.htm) predicted N-myristoylation sites for LOG2 and LUL1-4. Moreover, in vitro myristoylation of LUL1 was recently demonstrated (Yamauchi et al, 2010). To experimentally verify that LOG2 could be myristoylated, LOG2 and the corresponding G2A mutant (bearing a substitution known to inhibit N-terminal myristoylation; Gordon et al, 1991) were expressed in rabbit reticulocyte lysate-coupled transcription-translation systems in the presence of [ 3 H]myristic acid or [ 3 H]Leu.…”
Section: Myristoylation Of Log2 Is Important For Its Membrane Localizmentioning
confidence: 99%